A Crime Scene Fabricated as Suicide - Amararatne, R.R.G.S.; Vidanapathirana, M. (Journal of Clinical and Diagnostic Research, India., 2017)
When ascertaining the manner of death, the forensic pathologist should be careful, because in some instances, attempts are made by the criminals to conceal homicides as suicides. The case under discussion highlights the contribution of the forensic pathologist in the ascertainment of the manner in firearm deaths. The deceased was a poacher and his dead body was found in a cashew land with his shotgun lying over him. The shirt had a roughly circular defect with muzzle mark, and burnt and blackened margin. Beneath that, on front of the left upper chest a 2cm diameter circular, perforated laceration, with muzzle imprint and, burnt and blackened margin was found. Shelving was found at the upper margin. Chest X-ray showed the downward pellet distribution. Cause of death was chest injuries due to pellets discharged from a smooth bore weapon. Length of the upper arm reach was 65cm (25 inches) and the length from the muzzle to the trigger was 79cm (31 inches). In conclusion, it was found to be a fabricated suicide scene and the manner of death was ascertained as homicide. This reiterates that the postmortem investigation of firearm deaths should be performed or conducted under direct supervision of forensic specialist to deliver justice.
Keywords: Arm reach, Direction of fire, Shotgun